2021
DOI: 10.1016/j.csbj.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial type II toxin-antitoxin systems acting through post-translational modifications

Abstract: The post-translational modification (PTM) serves as an important molecular switch mechanism to modulate diverse biological functions in response to specific cues. Though more commonly found in eukaryotic cells, many PTMs have been identified and characterized in bacteria over the past decade, highlighting the importance of PTMs in regulating bacterial physiology. Several bacterial PTM enzymes have been characterized to function as the toxin component of type II TA systems, which consist of a toxin that inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…TA systems are ubiquitous genetic module found in varieties of bacteria and archea that could participate in various physiological processes, such as phage abortive infections, metabolism, cell growth, and viability during stress conditions ( 29 ). Type II TA systems are the most abundant genetic modules in bacterial species, in which both toxin and antitoxin form tight noncovalent complex.…”
Section: Discussionmentioning
confidence: 99%
“…TA systems are ubiquitous genetic module found in varieties of bacteria and archea that could participate in various physiological processes, such as phage abortive infections, metabolism, cell growth, and viability during stress conditions ( 29 ). Type II TA systems are the most abundant genetic modules in bacterial species, in which both toxin and antitoxin form tight noncovalent complex.…”
Section: Discussionmentioning
confidence: 99%
“…N, the number of times the experiment was performed. *p < 0.05; **p < 0.01 Yashiro et al, 2020;Zhang et al, 2020). E. piscicida has gradually become a primary pathogen that threatens global aquaculture, and it has attracted increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the diversity and importance of its role, the type II TA system has become the basis for more research (Dai et al, 2021; Klemenčič et al, 2021; Yashiro et al, 2020; Zhang et al, 2020). E .…”
Section: Discussionmentioning
confidence: 99%
“…The ectopic expression of toxins belonging to TA systems leads to growth inhibition in either a bactericidal or a bacteriostatic manner. Several studies have shown that toxins inhibit important metabolic processes such as translation, cell division, cell wall assembly and DNA replication [1,2,[6][7][8][9]. The antitoxin autoregulates the expression of the TA system and neutralizes the activity of the cognate toxin [1,10,11].…”
Section: Introductionmentioning
confidence: 99%